Wilson Disease Prevalence: Discrepancy Between Clinical Records, Registries and Mutation Carrier Frequency. Issue 2 (February 2022) - Lorente-Arencibia, Pascual; García-Villarreal, Luis; González-Montelongo, Rafaela; Rubio-Rodríguez, Luis A.; Flores, Carlos; Garay-Sánchez, Paloma; delaCruz, Tanausú; Santana-Verano, Milagros; Rodríguez-Esparragón, Francisco; Benitez-Reyes, Juana N.; Fernández-Fuertes, Fernando; Tugores, Antonio
ABSTRACT: Objectives: Diagnosis of Wilson disease (WD) is difficult and, as early detection may prevent all symptoms, it is essential to know the exact prevalence to evaluate the cost-efficacy of a screening program. As the number of WD patients was high in our population, we wished to estimate prevalence by determining the carrier frequency for clinically relevant ATP7B mutations. Methods: To estimate prevalence, screening for the most prevalent mutation was performed in 1661 individuals with ancestry in Gran Canaria, and the frequency of other mutations was estimated from patient records. Alternatively, ATP7B mutations were detected from exomes and genomes from 851 individuals with Canarian ancestry, 236 from Gran Canaria, and a public Spanish exome database. Results: Estimated carrier frequencies in Gran Canaria ranged from 1 in 20 to 28, depending on the method used, resulting in prevalences of 1 case per 1547 to 3140 inhabitants. Alternatively, the estimated affected frequencies were 1 in 5985 to 7980 and 1 in 6278 to 16, 510 in the archipelago or mainland Spain respectively. Conclusions: The number of carriers predicts much higher prevalences than reported, suggesting that WD is underdiagnosed; specific mutations may remain unnoticed due to low penetrance or no signs of disease at all; regional prevalence rather than national prevalence should be considered in cost-efficacy models to approach preventive screening in the asymptomatic population and genetic screening strategies will have to deal with the genetic heterogeneity of ATP7B in the general population and in patients. Abstract : Supplemental Digital Content is available in the text